EFFECT OF WORKLOAD AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE OF PT. XX WITH JOB SATISFACTION AS INTERVENING VARIABLE - Malau, Thoho Sarjan; Kasmir, Kasmir (Dinasti International Journal of Digital Business Management, 2021)
The purpose of this study is to examine the effect of workload and work discipline on performance with job satisfaction as an intervening variable. The number of respondents involved in this study reached 107 respondents. All respondents are employees at PT. XX, both employees who occupy staff positions and employees who have positions as leaders/managers of the company. This research is a quantitative research. Research data obtained from the results of filling out the questionnaire. The research data was then analyzed through the Partial Least Square analysis technique with the SmartPLS program. The results of the analysis using the PLS analysis technique provide the following conclusions: (1) Workload has a negative effect on job satisfaction; (2) work discipline has a negative effect on job satisfaction; (3) Workload has a negative effect on performance; (4) Work discipline has a positive effect on performance; (5) Job satisfaction has a positive effect on performance; (6) Workload can affect performance through job satisfaction; (7) Work discipline can affect performance through job satisfaction.